The process of rehabilitation of mined forest lands toward degraded forest ecosystem recovery in Kalimantan, Indonesia - TRIYONO SUDARMADJI; WAHJUNI HARTATI (Biodiversitas Journal of Biological Diversity, 2016)
Sudarmadji T, Hartati W. 2016. The process of rehabilitation of mined forest lands toward degraded forest ecosystem recovery in Kalimantan, Indonesia. Biodiversitas 17: 185-191. An overview of mined forest lands at East and Central Kalimantan Indonesia was conducted to determine most important influencing factors supporting degraded forest ecosystem recovery. Consecutivestages of rehabilitation processes consist of reclamation-backfilling, re-contouring, re-shaping, topsoils spreading, and revegetationland preparation, planting, maintenance covering minimum topsoils spreading, soil acidity, plant hole size, soil improvement application (dolomite, organic-inorganic fertilizers), vegetation planting vegetation planting (plant species selection-quality and site matching-verified plantmaterial sources, hardening-off, planting techniques), and land management implementation. The potential degraded forest ecosystem recovery was shown by cover crops and fast growing species plant and undergrowths, survive primary species, decreasing surface runoff/overland flows following increasing soil infiltration capacities, decreasing soil erosion rate and it’s erosion hazard, and an improved environments as habitat for invading wildlifes. The general characteristics of potential degraded forest ecosystem recovery after rehabilitation processes are: spread soil materials thickness > 70 cm, bulk density + 1,2 g.ml-1, soil acidity > 5,5, macro nutrients (N, P, K, Ca, Mg)-low to moderate, decreasing overland water flow following increasing soil infiltration capacity-moderate to high, decreasing soil erosion rate-very low to moderate, decreasing erosion hazard level-very slight to moderate, growing plants of fast growing species with significant layers and land cover, and growing interline planted primary species. Viewed from the ecological aspect, in the revegetated degraded forest lands wildlife such as insects, birds, reptiles, amphibians and small mammals were found feeding and alsopermanently living in ecosystem regeneration following gradual habitat improvement. The ecosystem status was identified as a progression towards degraded forest ecosystem recovery.